PENGARUH LATIHAN AKURASI SHOOTING BERVARIASI DALAM PERMAINAN SEPAK BOLA SSB RBS SOCCER SCHOOL - Anggarianto, Emil; Jalil, Rasyidah; Kahar , Irsan; Dahlan, Firmansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Shooting ability is an important skill in soccer that determines the success of scoring goals. Improving this ability requires proper physical training to optimize muscle strength, coordination, and kicking accuracy. This study aims to determine the effect of various shooting accuracy training in soccer games at SSB RBS Soccer School. The research method used is a quantitative experiment with a one-group pretest-posttest design, where an initial measurement (pretest) was taken before treatment and a final measurement (posttest) after treatment. The study population was 43 players, while the sample consisted of 15 people selected by random sampling. The varied shooting accuracy training program was implemented for 18 meetings which included pretest and posttest data collection. Shooting ability was measured by a kick test from a distance of 15 meters towards a soccer goal that had been given a target net. The results of the paired sample t-test showed a significant difference between the pretest and posttest scores, with an average difference of 3.47 points and a significance value of p = 0.011 (p < 0.05). It can be concluded that the training provided is very effective in increasing leg muscle strength, coordination, and body stability which contributes directly to improving shooting abilities in the soccer game of SSB RBS Soccer School players.